A Route to Chaotic Behavior of Single Neuron Exposed to External Electromagnetic Radiation - Feng, Peihua; Wu, Ying; Zhang, Jiazhong (Frontiers in Computational Neuroscience, 2017)
Nonlinear behaviors of a single neuron described by Fitzhugh-Nagumo neuron model, with external electromagnetic radiation considered, is investigated. It is discovered that with external electromagnetic radiation in form of a cosine function, the mode selection of membrane potential occurs among periodic, quasi-periodic and chaotic motions as increasing the frequency of external transmembrane current, which is selected as a sinusoidal function. When the frequency is small or large enough, periodic and quasi-periodic motions are captured alternatively. Otherwise, when frequency is in interval 0.778<ω<2.208, chaotic motion characterizes the main behavior type. The mechanism of mode transition from quasi-periodic to chaotic motion is also observed when varying the amplitude of external electromagnetic radiation. The frequency apparently plays a more important role in determining the system behavior.